A national study of the provision of oncology sperm banking services among Canadian fertility clinics. (4th February 2013) - Yee, S.; Buckett, W.; Campbell, S.; Yanofsky, R.A.; Barr, R.D.
<x xml:space="preserve">Abstract</x> The purpose of this study was to survey the current state of oncology sperm banking services provided by fertility clinics across Canada. A total of 78 Canadian fertility facilities were invited to complete a questionnaire related to the availability, accessibility, affordability and utilisation of sperm banking services for cancer patients. The total response rate was 59%, with 20 (69%) in vitro fertilisation clinics and 26 (53%) other fertility centres returning the survey. A total of 24 responding facilities accepted oncology sperm banking referrals. The time frame to book the first banking appointment for 19 (79%) facilities was within 2 days. Inconsistent practice was found regarding the consent process for cancer patients who are of minority age. Eight (33%) facilities did not provide any subsidy and charged a standard banking fee regardless of patients' financial situations. Overall, the utilisation of oncology sperm banking services was low despite its availability and established efficacy, suggesting that Canadian cancer patients are notably underserved. The study has highlighted some important issues for further consideration in improving access to sperm banking services for cancer patients, especially for adolescents. Better collaboration between oncology and reproductive medicine to target healthcare providers would help to improve sperm banking rates.